Suppression of Bactrocera oleae (Diptera: Tephritidae) pupae by soil arthropods in the olive grove - Dinis, Ana Maria (2018)
Soil arthropods can provide ecosystem services, such as biological control of crop pests that spend part of their life cycle in the soil. This is the case of Bactrocera oleae (Rossi) (Diptera: Tephritidae), one of the most important pests of olives. The impact of edaphic arthropods on the abundance of B. oleae pupae was evaluated and their contribution for biological control of the pest was quantified. Exclusion and exposed boxes with B. oleae pupae were installed in olive groves in parallel with pitfall traps used for sampling arthropods and the percentage of pupae suppression was evaluated from January to May 2014. Forficulidae dominated the community during the winter period while Formicidae dominated in spring. Pupae suppression reached the maximum value in the beginning of spring and these results indicate that soil arthropods have strong impact in the decline of B. oleae pupae in olive groves.